Gender, Social Change and Urbanisation in Four North Indian Clusters. (September 2021) - Kapur, Devesh; Sircar, Neelanjan; Vaishnav, Milan
Urbanisation in India is reshaping established social and economic patterns of behaviour in ways that scholars are struggling to analyse. This article introduces this special issue presenting new empirical research on the interconnections between gender, social change and urbanisation in India. It does so by relying on a unique dataset drawn from nearly 15, 000 households across four consequential urban clusters—Dhanbad, Indore, Patna and Varanasi—in North India. The collection of articles in this issue informs new inquiries into women's employment, women's agency and the construction and shaping of social attitudes. Specifically, the articles disentangle the practical barriers to women's economic empowerment, measure how employment and household dynamics shape women's agency and explore ways in which status hierarchies and variation in access to information colour women's social attitudes and political preferences. Collectively, they demonstrate the uneven nature of gender empowerment in the shadow of an urbanising, but highly stratified economy and society.